Epigenetic modifications involving ncRNAs in digestive system cancers: focus on histone modification - Xiaodi Yin; Jingyi Li; Jiahui Zhao; Weihan Zheng; Aohua Zhang; Jun Ma (Clinical Epigenetics)
Abstract In recent years, epigenetic modifications have been strongly linked to tumor development, with histone modifications representing a key epigenetic mechanism. In addition, non-coding RNAs (ncRNAs) play a critical role in regulating cancer-related pathways. The abnormal interaction between histone modifications and ncRNAs, both pivotal epigenetic regulators, has been widely observed across various cancer types. Here, we systematically explore the molecular mechanisms through which histone modifications and ncRNAs contribute in the pathogenesis of digestive system cancers, and aberrant ncRNA-mediated histone modifications manipulate various biological behaviors of tumor cells including proliferation, migration, angiogenesis, etc. In addition, we provide new insights into diagnostic, prognostic markers, therapeutic targets and chemoradiation resistance for digestive system cancers from the epigenetic perspective.